Patents and Patent Searching - Alice K. Kawakami (Issues in Science and Technology Librarianship)
The definition, requirements for and types of patents are discussed as well as tools available to access patents. Steps needed to perform a patent subject search are delineated. Includes World Wide Web resources for information on patents and searching access to patents.